Maternal satisfaction with joint and sole child physical placement arrangements following separation in Wisconsin and Finland - Riser Quentin H.; Haapanen Mari; Bartfeld Judith; Berger Lawrence M.; Hakovirta Mia; Meyer Daniel; Miettinen Anneli (WILEY, 2022)
Families (and sometimes courts) make important decisions regarding child physical custody arrangements post-separation, and shared parenting arrangements are increasingly common in most developed countries. Shared arrangements may be differentially associated with parental satisfaction, and these associations may vary across countries. Using data from surveys of separated mothers in Wisconsin and Finland, the present study explores this possibility and is guided by three aims: (a) to identify child and family characteristics associated with sole and shared child placements 6 or more years after separation; (b) to estimate associations of children's post-separation placements with maternal satisfaction with placements and expense sharing; (c) to examine whether the relationship between post-separation placement and maternal satisfaction varies by mothers' earnings and the quality of parents' relationships. We find that Finnish mothers with shared placement are more satisfied with their placement than are their counterparts with sole placement, while we find the inverse is true for Wisconsin mothers. Moreover, parental satisfaction with shared placement, overall and relative to sole placement, varies greatly depending on the quality of a mother's relationship with the other parent; and differences in relationship quality in Wisconsin and Finland may help explain the difference in satisfaction with shared placement in the two locations. In both Finland and Wisconsin, we find mothers with shared placement are more satisfied with the way expenses are shared between parents than are mothers with sole placement. Associations between placement and satisfaction are robust to extensive controls for child and maternal characteristics.